2020
DOI: 10.2147/opth.s269524
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Attitude, and Practices (KAP) of Diabetics Towards Diabetes and Diabetic Retinopathy in Riyadh, Saudi Arabia: Cross-Sectional Study</p>

Abstract: Background: Diabetes mellitus (DM) and its complication present a major morbidity burden among Saudi population. Awareness and proper knowledge of this highly prevalent disease is crucial to enhance early detection and proper intervention. Therefore, the main aim of this study was to identify the knowledge, attitude, and practices (KAP) of diabetic patients towards diabetes and diabetic retinopathy in Riyadh, Saudi Arabia. Methods: This cross-sectional study was conducted in 50 randomly selected primary care c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(37 reference statements)
1
10
1
Order By: Relevance
“…25 Nevertheless, the median knowledge score of participants in this study was 6 and more than 62% toward the poor tier. The median knowledge score for diabetes was 10 (good knowledge range 9–17), according to Al-Yahya et al 18 The average knowledge score for DM was good among our participants, which is comparable with another research performed in Fiji by Zibran et al, who found a good level of knowledge with a mean knowledge score of 23.3 out of 30 (SD 3.25). 26 In India, on the other hand, John et al found that 58% of their sample lacked good knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…25 Nevertheless, the median knowledge score of participants in this study was 6 and more than 62% toward the poor tier. The median knowledge score for diabetes was 10 (good knowledge range 9–17), according to Al-Yahya et al 18 The average knowledge score for DM was good among our participants, which is comparable with another research performed in Fiji by Zibran et al, who found a good level of knowledge with a mean knowledge score of 23.3 out of 30 (SD 3.25). 26 In India, on the other hand, John et al found that 58% of their sample lacked good knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…Blood sugar control as a preventive measure for DR was acknowledged by 69.9% of the patients. These results were different from what was found in Riyadh, as only 22.8% of the respondents there believed that a poor glycemic control was an essential factor that worsens diabetic retinopathy [ 14 ]. These results highlight the importance of encouraging patients to adhere to the follow-ups scheduled with their ophthalmologists regardless of the blood sugar levels because DR can be asymptomatic in some patients.…”
Section: Discussioncontrasting
confidence: 61%
“…This is in line with the findings of previous studies. In Riyadh, Saudi Arabia, 28.7% of diabetics believed that they needed a screening once every year [ 14 ], while in Jordan only 20.7% thought that an eye examination should be done annually, [ 15 ] and 41.9% of people in Turkey believed that an annual eye check is required [ 16 ]. The follow-up frequencies need to be elaborated more by ophthalmologists.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of knowledge about DR was significantly associated with educational level alone, and the odds of subjects with a primary and middle level of education having a good knowledge of it were 0.1 (0.0, 0.2) and 0.2 (0.1, 0.6) times the odds for those with a high level of education. Similar studies from eastern China ( 10 ), Saudi Arabia ( 11 ) and India ( 12 , 13 ) found that those with a lower level of education were less likely to be aware of DR. Since educational attainment is an important measurement of socioeconomic parameters, these people are more likely to be of a lower socioeconomic status and may not be able to afford the expenses for attending eye clinics when their vision is impaired.…”
Section: Discussionmentioning
confidence: 52%